The ExbD Periplasmic Domain Contains Distinct Functional Regions for Two Stages in TonB Energization - Ollis, Anne A. (American Society for Microbiology, 2012)
The TonB system of Gram-negative bacteria energizes the active transport of diverse nutrients through high-affinity TonB-gated outer membrane transporters using energy derived from the cytoplasmic membrane proton motive force. Cytoplasmic membrane proteins ExbB and ExbD harness the proton gradient to energize TonB, which directly contacts and transmits this energy to ligand-loaded transporters. In Escherichia coli, the periplasmic domain of ExbD appears to transition from proton motive force-independent to proton motive force-dependent interactions with TonB, catalyzing the conformational changes of TonB. A 10-residue deletion scanning analysis showed that while all regions except the extreme amino terminus of ExbD were indispensable for function, distinct roles for the amino- and carboxy-terminal regions of the ExbD periplasmic domain were evident. Like residue D25 in the ExbD transmembrane domain, periplasmic residues 42 to 61 facilitated the conformational response of ExbD to proton motive force. This region appears to be important for transmitting signals between the ExbD transmembrane domain and carboxy terminus. The carboxy terminus, encompassing periplasmic residues 62 to 141, was required for initial assembly with the periplasmic domain of TonB, a stage of interaction required for ExbD to transmit its conformational response to proton motive force to TonB. Residues 92 to 121 were important for all three interactions previously observed for formaldehyde-cross-linked ExbD: ExbD homodimers, TonB-ExbD heterodimers, and ExbD-ExbB heterodimers. The distinct requirement of this ExbD region for interaction with ExbB raised the possibility of direct interaction with the few residues of ExbB known to occupy the periplasm.